2010
DOI: 10.1002/art.27709
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular injection of heparin‐binding insulin‐like growth factor 1 sustains delivery of insulin‐like growth factor 1 to cartilage through binding to chondroitin sulfate

Abstract: Objective. Insulin-like growth factor 1 (IGF-1) stimulates cartilage repair but is not a practical therapy due to its short half-life. We have previously modified IGF-1 by adding a heparin-binding domain and have shown that this fusion protein (HB-IGF-1) stimulates sustained proteoglycan synthesis in cartilage. This study was undertaken to examine the mechanism by which HB-IGF-1 is retained in cartilage and to test whether HB-IGF-1 provides sustained growth factor delivery to cartilage in vivo and to human car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 58 publications
0
47
0
Order By: Relevance
“…Often accompanied by damage to other joint tissues, such injuries lead to PTOA with high incidence. Potential disease-modifying OA drugs (DMOADs), including anti-catabolic glucocorticoids (Grodzinsky et al , 2017; Huebner et al , 2014) and pro-anabolic growth factors (Fortier et al , 2001; Miller et al , 2010), have been identified as being able to reverse or prevent PTOA. However, to date, clinical trials evaluating DMOAD candidates have failed due to systemic toxicity or lack of evidence of sustained benefit and/or effective cartilage targeting (Evans et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Often accompanied by damage to other joint tissues, such injuries lead to PTOA with high incidence. Potential disease-modifying OA drugs (DMOADs), including anti-catabolic glucocorticoids (Grodzinsky et al , 2017; Huebner et al , 2014) and pro-anabolic growth factors (Fortier et al , 2001; Miller et al , 2010), have been identified as being able to reverse or prevent PTOA. However, to date, clinical trials evaluating DMOAD candidates have failed due to systemic toxicity or lack of evidence of sustained benefit and/or effective cartilage targeting (Evans et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A new fusion protein made by adding the heparin-binding domain of heparin-binding EGF to IGF-1 (ie, HB-IGF-1) is amenable to delivery in mature articular cartilage [36,49]. A single dose of HB-IGF-1 resulted in sustained delivery and stimulation of proteoglycan synthesis for at least 8 days.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation, the authors found that HpB-IGF-1 was primarily retained in articular cartilage through binding to both ChS of aggrecan, while retaining an high affinity for HS chains of perlecan. 62 This property may be crucial to avoid sequestration of the drug in the territorial and inter-territorial zones and enable the transport to the pericellular zone and successive interaction with chondrocytes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%